Squatting Biomechanics After Femoroacetabular Impingement Surgery: A Systematic Review and Meta-analysis - Generoso, Talissa O; Pelegrinelli, Alexandre R M; Gonzalez, Felipe F; Pallone, Lucas V; Locks, Renato; Guadagnin, Eliane C; Chahla, Jorge; Gustafson, Jonathan A; Metsavaht, Leonardo; Leporace, Gustavo (Clinical journal of sport medicine, 2025)
Femoroacetabular impingement syndrome (FAIS) is a prevalent cause of hip pain, characterized by distinctive motion patterns. However, the impact of surgical intervention on squatting biomechanics remains underexplored. This review aims to evaluate the effects of surgical treatment on biomechanical outcomes during squatting in patients with FAIS. A comprehensive search was conducted across multiple databases following PRISMA guidelines (Prospero registration number CRD42023473974). Data of longitudinal, prospective/retrospective cohorts, case-control, and clinical trial studies with 3-dimensional motion analysis describing kinematics and/or kinetics for any joint during squatting in patients with FAIS comparing presurgical to postsurgical biomechanical data on the same patients were included. Quality assessment was performed using MINORS criteria. Both qualitative and quantitative analyses were performed. Six studies met the inclusion criteria for qualitative review and 5 were suitable for meta-analysis. The overall quality of the studies was moderate based on MINORS criteria. The postsurgical motion analysis was performed between 6 and 32 months postoperatively. Although most studies reported no significant changes in kinematic or kinetic variables postsurgery, individual studies reported specific increases in squat depth, pelvic sagittal range of motion, anterior pelvic tilt, hip and knee flexion, and ankle dorsiflexion angles. Meta-analysis revealed no significant differences in the kinematic parameters analyzed. These findings underscore the multifaceted nature of FAIS, suggesting that bone deformities alone do not account for the biomechanical limitations observed during squatting in these patients. This highlights the need for further biomechanical investigations. Systematic Review of Level II-III studies.